Bridging Religion, Science, and Spirituality: A Holistic Approach to Peace and Understanding - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2024)
This study explores the integration of religious organizations and spirituality with scientific approaches to foster global peace and address contemporary challenges. It highlights the shared values of interconnectedness and compassion within both domains, emphasizing the potential for collaboration in addressing urgent issues such as climate change, social justice, and mental health. The findings reveal that interdisciplinary initiatives, such as peace education programs that blend scientific knowledge with spiritual teachings, can effectively promote empathy and understanding among diverse communities. Furthermore, the study discusses the role of sustainable development, where religious organizations can advocate for ecological stewardship, thus bridging the gap between faith-based initiatives and scientific research. Technological advancements, particularly in digital communication, present new opportunities for disseminating messages of peace and facilitating interfaith dialogue. Recommendations include fostering collaboration between religious leaders and scientists, supporting community-based initiatives in science and spirituality, and promoting research that explores their intersections. Ultimately, this research underscores the importance of an integrated approach that combines scientific inquiry with spiritual values to address the root causes of conflict and build a more harmonious future.